Finite element simulation on precast beam-to-column joint under column removal scenario - Kong, Kok Khuen (Nanyang Technological University, 2021)
With the possibility of a terrorist attack lingering high, government authorities are paying close attention to a building's ability to prevent progressive failure. By implementing a column removal scenario, the alternate load path (ALP) technique is one of the direct methods for assessing progressive collapse resistance. To fill this knowledge gap, the author conducted a 3-D solid element numerical simulation to determine the behaviour of concrete beam-to-column connection by column removal scenario in this project. The experimental results for three different models (1 monolithic and 2 precast connections) from two research papers were validated. It was found that ABAQUS was a powerful software as it was able to predict the FEM results and failure mode accurately compared to experimental results. After FEM validation, a series of parametric studies were carried on. The monolithic connections had changes in middle reinforcement ratio, while the other two precast structures had different enhanced connection details such as grouting, installation of the top-seat-angle and steel plate. In this study, it was found out that flexural action, compressive arch action (CAA) and catenary action (CA) were mobilized for the revised monolithic connection. However, CA was not formed for the revised precast connection. Besides, the author discovered that an increase in middle reinforcement ratio provided a greater structural capacity and ductility to the connection. Also, the closer the middle reinforcement to the top implies a higher capacity and ductility. The increase in the ultimate capacity of the revised connection of precast connection is in the order of grouting the empty gap, installation of steel top-seat angle and installation of the steel side plate. Finally, the grouting of the gap can improve initial stiffness of joints.